Fabrication of UV-C photodetector with ultimate stability in extreme space environments (radiation, low temperature) using aerosol-deposited Ga2O3 - Cho, Hyeon Ho; Lee, Sang Hoon; Kim, Dahoon; Yu, Hak Ki; Choi, Jae Young; Park, Jae Hyuk (Ceramics International, 2023)
We report on the fabrication and characterization of a Ga2O3-based UV-C photodetector using the aerosol deposition (AD) method. By optimizing the size and crystallinity of the Ga2O3 powder, we were able to obtain a uniform thin film with high transmittance (70–80%) without the need for additional heat treatment or high vacuum environments. The resulting Ga2O3 film exhibited a high and selective response to 254 nm wavelength light, even without any treatment, and remained stable when exposed to γ-radiation. The photodetector also performed well in extreme temperatures (−196 °C–150 °C), making it suitable for use in harsh environments, such as the space industry. Our findings demonstrate the potential of the AD method for the fabrication of high-quality Ga2O3 thin films for photodetector applications.
Keywords: Aerosol deposition; Aerosol deposition method; Environment radiation; Extreme environment; Ga2O3 thin film; Lows-temperatures; Space environment; Thin-films; UV-C; γ-radiation; Aerosol deposition; Extreme environment; Ga2O3 thin film; UV-C; γ-radiation